2005
DOI: 10.1161/circulationaha.104.532234
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutation in Desmoplakin Causes Arrhythmogenic Left Ventricular Cardiomyopathy

Abstract: Background-Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a familial heart muscle disease characterized by structural, electrical, and pathological abnormalities of the right ventricle (RV). Several disease loci have been identified. Mutations in desmoplakin have recently been isolated in both autosomal-dominant and autosomal-recessive forms of ARVC. Primary left ventricular (LV) variants of the disease are increasingly recognized. We report on a large family with autosomal-dominant left-sided ARVC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
165
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(183 citation statements)
references
References 18 publications
11
165
0
7
Order By: Relevance
“…Fat infiltration of the right ventricle is usually considered a mandatory finding for the diagnosis, but the diagnosis should not be based only on the presence of fat because normal hearts may show a certain degree of fatty infiltration in the right ventricle. We have shown that it is not unusual to see fat infiltration occupying over 50% of myocardial area in the anterior wall of the right ventricle in trauma victims (autopsy control subjects; Burke et al, 1998 ARVD is a genetic cardiomyopathy that has been associated with mutations of plakoglobin, plakophalin, and desmoplakin genes (Norman et al, 2005). These genes encode desmososmal proteins which are involved with cell adhesion.…”
Section: Arrhythmogenic Right Ventricular Dysplasiamentioning
confidence: 86%
“…Fat infiltration of the right ventricle is usually considered a mandatory finding for the diagnosis, but the diagnosis should not be based only on the presence of fat because normal hearts may show a certain degree of fatty infiltration in the right ventricle. We have shown that it is not unusual to see fat infiltration occupying over 50% of myocardial area in the anterior wall of the right ventricle in trauma victims (autopsy control subjects; Burke et al, 1998 ARVD is a genetic cardiomyopathy that has been associated with mutations of plakoglobin, plakophalin, and desmoplakin genes (Norman et al, 2005). These genes encode desmososmal proteins which are involved with cell adhesion.…”
Section: Arrhythmogenic Right Ventricular Dysplasiamentioning
confidence: 86%
“…[19][20][21] Interestingly, other missense and nonsense mutations in the desmoplakin gene have been associated with isolated dominant ARVD/C or arrhythmogenic left ventricular cardiomyopathy in which affected patients had no hair or skin abnormalities. [22][23][24] Furthermore other DSP mutations have been found to cause cutaneous abnormalities without signs of cardiomyopathy. 25,26 DSP mutations are summarized in Figure 2B.…”
Section: Desmoplakinmentioning
confidence: 99%
“…These results, along with the various desmoplakin mutations associated with human genetic disorders (please see below) support a strong role for desmoplakin in the assembly and interlinking of desmosomes to desmin intermediate filaments in cardiomyocytes. Peifer et al, 1992;Cowin et al, 1986 Systemic KO Embryonic lethal Bierkamp et al, 1996;Ruiz et al, 1996 Cardiac Specific KO Premature death due to cardiac dysfunction Li et al, 2011 Plakophilin-2 Mertens et al, 1996;Mertens et al, 1999 Systemic KO Embryonic lethal Desmoplakin Franke et al, 1982 Systemic KO Embryonic lethal Norgett et al, 2000Rampazzo et al, 2002Norman et al, 2005Yang et al, 2006Uzumcu et al, 2006Bolling et al, 2010Bauce et al, 2010 …”
Section: Plakinsmentioning
confidence: 99%
“…Importantly, the reduced expression or complete absence of plakoglobin from the ID of ARVC patients is a consistent feature, making it a valuable marker for its diagnosis, which still remains problematic with many cases being un-or misdiagnosed. Mutations in the gene encoding desmoplakin have been identified as the underlying cause of a variation of Naxos disease, referred to as Carvajal syndrome that is also characterized by woolly hair, palmoplantar keratoderma and cardiac disease (Kaplan et al, 2004a;Kaplan et al, 2004b;Norman et al, 2005;Rampazzo et al, 2002;Saffitz, 2009;Yang et al, 2006;Bauce et al, 2010;Bolling et al, 2010;Norgett et al, 2000;Uzumcu et al, 2006). Notably, cardiac disease is presented as a generalized hypertrophy and dilation, involving both the right and left ventricles, and accompanied by focal ventricular aneurysms without any apparent fibrofatty tissue replacement (Kaplan et al, 2004a;Yang et al, 2006).…”
Section: Id Proteins In Human Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation